Physical and mechanical properties of a vegetable oil based nanocomposite - Buffa, Juan Manuel (2018)
Nanocomposites films were prepared from a bio-based waterborne polyurethane and cellulose nanocrystals (CNCs) obtained from the sulfuric acid hydrolysis of cellulose nanofibers. The polyurethane used as matrix of the nanocomposite film was synthesized from a biobased macrodiol derived from castor oil, 2,2-bis(hydroxymethyl)propionic acid, 1,6-hexamethylene diisocyanate and triethylamine. The concentration of CNC in the films was varied from 0 to 10 wt.%, and the films obtained by casting were characterized by DSC, DMA, tensile tests and TGA. Due to the hydrophilic nature of the PU, the nanocrystals were well dispersed, obtaining homogenous and transparent films which displayed improved thermal and mechanical properties compared to the neat PU. The impact of the CNCs on the crystallization of the polymer was analyzed. Finally, the mechanical properties were fitted to well known theoretical models, allowing a better understanding of the interactions between polymer and filler in the composites.